Students' Perception of Guided Inquiry Learning in Physics Viewed from Collaboration Skills and Scientific Attitude - Hafiz Suhendra; Yennita Yennita; Dedi Irawan (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to determine the students’ perceptions of Guided Inquiry learning on physics and the effect of learning on collaboration abilities and scientific attitudes. This research is survey research. The subjects in this study consisted of 36 students from class X MIPA 1 MAN 1 Siak in the 2022/2023 academic year. The research instrument consisted of 20 statement items, including 8 Guided Inquiry statement items, 7 Guided Inquiry learning effects statement items on collaboration skills, and 5 Guided Inquiry learning effect statement items statement on students' scientific attitudes. Data on students' perceptions of Guided Inquiry learning were analyzed by descriptive analysis. The results of this study indicate that 39 students' collaboration abilities are in a low category and 40 students' scientific attitudes are in a low category. While the application of Guided Inquiry learning with a score of 59 is in the sufficient category. The conclusion of this study shows that the effect of Guided Inquiry learning on students' collaboration abilities is in a low category, the effect of Guided Inquiry learning on students' scientific attitudes is low and the use of Guided Inquiry learning has not been maximized so that it is necessary to use the Guided Inquiry learning model to improve collaboration abilities and scientific attitudes of high school students